The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/insects12121095
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Potential Distribution of Ticks in the Western Kanto Region, Japan: Predictions Based on Land-Use, Climate, and Wildlife

Abstract: Background: Tick distributions have changed rapidly with changes in human activity, land-use patterns, climate, and wildlife distributions over the last few decades. Methods: To estimate potential distributions of ticks, we conducted a tick survey at 134 locations in western Kanto, Japan. We estimated the potential distributions of six tick species (Amblyomma testudinarium Koch, 1844; Haemaphysalis flava Neumann, 1897; Haemaphysalis kitaokai Hoogstraal, 1969; Haemaphysalis longicornis Neumann, 1901; Haemaphysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For example, in countries with distinct wet and dry seasons, climatic factors may have a strong influence on mosquito-borne disease outbreaks beyond seasonal effects [ 57 ]. Moreover, animals with ticks move into residential areas, expanding the distribution area of various ticks [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in countries with distinct wet and dry seasons, climatic factors may have a strong influence on mosquito-borne disease outbreaks beyond seasonal effects [ 57 ]. Moreover, animals with ticks move into residential areas, expanding the distribution area of various ticks [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our tick survey collected 24,546 individuals of 4 genera and 16 tick species (Doi et al 2021). Notably, our MaxEnt models indicated that forest connectivity was most important for the 6 species under study.…”
mentioning
confidence: 89%
“…Summary of reports of A. testudinarium in the other four neighboring prefectures is as follows: one female was collected from an Asian black bear (Ursus thibetanus G. Cuvier, 1823) in Fukushima Prefecture (Kabeya et al, 2020), one case (number unknown) was recorded from Sika Deer (Cervus nippon Temminck, 1836 hereafter deer) (Yamaguti et al, 1971) and also a single specimen was collected by flagging from the Forestry and Forest Products Research Institute premises (Doi, 2022) from Ibaraki Prefecture, Doi et al (2021) collected more than one hundred specimens using the flagging method from nine collection sites in Gunma Prefecture, more than one hundred specimens from three wild boars (Sus scrofa Linnaeus, 1758) were reported in Saitama Prefecture (Takahashi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%